MINERAL-CHEMICAL AND STRUCTURAL FEATURES OF OPOKAMORPHIC OPAL-CRISTOBALITE ROCKS AS RAW MATERIAL FOR THE CONSTRUCTION INDUSTRY - Vladimir D. Kotlyar; Yuliya V. Terekhina (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
The relevance of the research is caused by the need to develop and involve opokamorphic opal-cristobalite rocks and their transitional varieties in the production of building materials for various purposes in the regions of distribution of these rocks – the central regions of Russia, the Volga region, Western Siberia, the North Caucasus. The main aim of the research is to develop criteria and methods for the assessment of opokamorphic opal-cristobalite rocks during geological work to determine the most promising directions of their use in the production of construction materials. Objects: explored deposits and large manifestations of opokamorphic opal-cristobalite rocks, which during geological work were evaluated narrowly and are not currently being developed or used in the production of construction materials and products. Methods: methods for determination of physical and mechanical properties of rocks; method of quantitative chemical analysis of rocks, X-ray phase studies, electron probe studies providing the possibility of elemental analysis in the range from Na to U; methods for carrying out technological tests according to the relevant technologies for the production of building materials and products. Decoding of diffractograms was carried out using appropriate methods, by comparison with such studies, as well as using international databases. Results. The authors have developed the classification of opokamorphic opal-cristobalite rocks by chemical and mineral composition as raw materials for the production of various types of building materials. There are four main classification criteria: the content of silica in the form of opal, the content of silica in the form of quartz, the content of aluminum oxide and calcium oxide. Six types of opokamorphic opal-cristobalite rocks were identified: silicified gaize, classical gaize, sandy gaize, clay gaize, carbonate gaize and clay-carbonate gaize. The developed classification allows, based on the data on the chemical and mineralogical composition of opokamorphic opal-cristobalite rocks, giving specific recommendations on their use for the production of certain types of building materials and predicting their properties.